Tuberculosis and HIV Coinfection - Gray, Jacob M.; Cohn, David L. (Seminars in Respiratory and Critical Care Medicine, 2013)
The human immunodeficiency virus (HIV) pandemic has amplified the global burden of tuberculosis (TB), particularly in sub-Saharan Africa, where 82% of the world's TB/HIV coinfection exists. HIV infection significantly increases the risk of developing and dying from TB and was associated with 350,000 TB deaths in 2010. The diagnosis of HIV-associated TB is often challenging due to atypical clinical and radiographic manifestations, more frequent extrapulmonary disease, and higher rates of smear-negative pulmonary TB. Nucleic acid amplification tests, including the Xpert MTB/RIF assay (Cepheid, Sunnyvale, CA), improve our ability to rapidly diagnose both smear-negative and extrapulmonary TB. The standard 6-month anti-TB regimen is usually adequate for HIV coinfected persons, but intermittent dosing in the intensive phase should be avoided because of an increased risk of relapse with acquired rifamycin resistance. The comanagement of HIV and TB is challenging due to drug–drug interactions, overlapping drug toxicities, concerns about adherence, and the immune reconstitution inflammatory syndrome. However, the initiation of antiretroviral therapy (ART) during the course of TB treatment is necessary to improve survival, and the appropriate timing of ART is dependent on the level of immune suppression. Therefore, the management of TB must be well coordinated with HIV resources, prepared to rapidly diagnose HIV, assess immune status, and correctly treat both infections.
Keywords: tuberculosis; HIV; AIDS; coinfection; antiretroviral therapy